2006
DOI: 10.1111/j.1474-919x.2006.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

What attracts birds to newly mown pasture? Decoupling the action of mowing from the provision of short swards

Abstract: Many bird species flock to forage on newly mown grass swards. Several potential benefits are offered by such swards, including increases in prey availability (flush of foliar prey, reduced physical obstruction to surface and soil prey) and a foraging environment with fewer visual obstructions, so allowing predators to be detected more easily. We performed a field experiment using captive Common Starlings Sturnus vulgaris foraging in bottomless enclosures on newly mown swards (within 1 h) and old mown swards (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Fuhlendorf et al 2009). Our study demonstrates that grass height and cover or each one alone, depending on the habitat requirements of individual species, determines habitat use by birds (Winter et al 2005;Devereux et al 2006;Donald et al 2010). Regional studies that link species abundance to habitat do not take into account detection (e.g.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Fuhlendorf et al 2009). Our study demonstrates that grass height and cover or each one alone, depending on the habitat requirements of individual species, determines habitat use by birds (Winter et al 2005;Devereux et al 2006;Donald et al 2010). Regional studies that link species abundance to habitat do not take into account detection (e.g.…”
Section: Discussionmentioning
confidence: 87%
“…Thick tall grass is worse than heavily grazed grass because of the possible effects of visual obstruction (e.g. Devereux et al 2006). This is important for ground nesting birds that breed and feed on the ground.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to high regrowth rates at the latitude of this study and at this time of year (rates of 60-100 kg dry matter/ha/day in May, and 50-80 kg dry matter/ha/day from June to August [Rural NI 2010]) it is likely that cut grass functionally becomes short grass relatively rapidly. For Common Starlings Sturnus vulgaris , it has been shown that capture efficiency of their soil-dwelling invertebrate prey was 71% greater on newly mown (within one hour) sward, than on sward mown to the same height 48 hours previously, although they did not spend any more time foraging on the former compared with the latter (Devereux et al 2006). We expect that the effects of such changes in micro-habitat caused by cutting would be analogous for Kestrel prey species, and that generally the advantages of freshly cut grass may be quite fleeting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the immediate effects of cutting on soil and surface invertebrates are likely to be less marked, with the most noticeable initial decline in abundance of the newly exposed prey probably due to depletion by foraging birds and other predators. Mowing of the grass will also alter the microclimate of the soil and sward, which is likely to cause invertebrates to disperse and their availability to decline naturally over time (Devereux et al 2006). This decline in prey abundance will result in a decline in foraging activity of those birds that feed on them.…”
Section: Discussionmentioning
confidence: 99%